Rare comorbidity of colon cancer, hepatic malignant mesothelioma, and abdominal Ewing’s sarcoma: a case report - Li, Yanru; Teng, Lukang; Wang, Shupeng; Wu, Xudong; Huang, Tianchen (Frontiers in Oncology, 2025)
We present a rare case of a patient with a history of colon cancer who subsequently developed hepatic mesothelioma and extraosseous Ewing’s sarcoma 10 years after surgery. The diagnosis of three completely different types of cancer in the same patient over a decade was confirmed through histopathological and immunohistochemical analysis. This case highlights the importance of clinicians maintaining a heightened awareness and clinical vigilance regarding multiple primary cancers, ensuring patients receive comprehensive diagnosis and treatment for improved prognosis and desired survival outcomes.